TiO2:Cex onto Al Clays for Photocatalytic Solar Water Disinfection - Belver, Carolina (2020)
A novel methodology was employed to prepare new nanocomposites with photocatalytic properties based on Ce-doped TiO2 nanoparticles arranged over a layered silicate. The catalysts were porous materials formed by exfoliated silicate layers surrounded by anatase nanoparticles. In this way, the anatase was doped by different amounts of Ce, yielding to catalysts with light absorption properties on the visible region. The photocatalytic behavior was tested for different reactions: adsorption and photocatalysis, showing outstanding and promising results for the removal of bacteria by using solar light as an energy source. The influence of the physicochemical properties of the catalyst and the reaction parameters will be studied in detail to manage new catalysts for the disinfection of drinking water.